PEMETAAN JARINGAN IRIGASI DI DAERAH TUKAD SABA DESA LOKAPAKSA - Misaq Akbar; I Wayan Treman; I Gst Ngr Yoga Jayantara (Jurnal ENMAP, 2023)
Seeing the many rice fields in Buleleng Regency. The total area of rice fields is not accompanied by the availability of data on irrigation conditions so that it becomes one of the obstacles. In addition, the average person uses the on screen method more often. this method turns out to be less accurate with conditions in the field, in contrast to the field survey method using GPS, the data obtained from the results of the field survey will be quite accurate, because we immediately go into the field and then it will be clear what the condition of the research object is. The method used is a qualitative descriptive method which analyzes the data in real terms. The results of the research obtained are the knowledge of irrigation networks in the Tukad Saba area. The real condition of the Tukad Saba irrigation area is 43.6% in a lightly damaged condition, 28.2% in a moderately damaged condition, 28.2% in a good condition, and 0% in severe damage from 39 condition points taken during the survey. field